The complex mosaic of Englishes. Issue 1 (3rd February 2016) - Rajagopalan, K.
Abstract : The English language is no longer any one nation's monopoly; practically every nation on earth has a stake in it. This is the overall thrust of the book in the spotlight. The amazing journey of the language from a none-too-conspicuous dialect once spoken on a part of a tiny island off the north-western coast of Continental Europe to a language of wider communication across the world is the topic that the book engages with. In the ten chapters that make up this book, Urszula Clark surveys the current state of the language in its worldwide spread, along with the inevitable phenomenon of the emergence of new regional varieties or 'Englishes'.